2014
DOI: 10.12720/jomb.3.4.282-287
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to PM10 and NO2 and Association with Respiratory Health among Primary School Children Living Near Petrochemical Industry Area at Kertih, Terengganu

Abstract: This study was carried out to determine the level of exposure to PM10 and NO2 and its relation to respiratory health among primary school children living near petrochemical industry area at Kertih, Terengganu. This cross sectional comparative study was conducted among 60 children from studied group and 60 children from comparative group. The respondents were selected based on inclusive criteria's for this study. Level of exposure of PM10 was measured using DustTrak Aerosol Monitor while level of exposure of NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 6 publications
0
18
0
1
Order By: Relevance
“…Some local research found that the increase of outdoor airborne pollutants mainly due to nearby industrial activities often linked with the increase in the prevalence of respiratory symptoms. In an instance, a study by some researcher has demonstrated that school children living in an exposed area within the vicinity of the petrochemical industry of Kerteh, Terengganu have significantly higher respiratory symptoms compared to non-exposed area [5]. Similar research conducted among preschool children in Selangor, Malaysia by Rawi further support the fact of higher prevalence of respiratory symptoms were experienced among children who attended preschools in the area with heavy traffic density [19].…”
Section: Respiratory Symptomsmentioning
confidence: 67%
See 2 more Smart Citations
“…Some local research found that the increase of outdoor airborne pollutants mainly due to nearby industrial activities often linked with the increase in the prevalence of respiratory symptoms. In an instance, a study by some researcher has demonstrated that school children living in an exposed area within the vicinity of the petrochemical industry of Kerteh, Terengganu have significantly higher respiratory symptoms compared to non-exposed area [5]. Similar research conducted among preschool children in Selangor, Malaysia by Rawi further support the fact of higher prevalence of respiratory symptoms were experienced among children who attended preschools in the area with heavy traffic density [19].…”
Section: Respiratory Symptomsmentioning
confidence: 67%
“…The parent-assisted method of questionnaire completion was applied among the participants. The sample size was estimated based on the previous prevalence of respiratory symptoms conducted by a group researcher [5].…”
Section: Questionnaire Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Ayuni et al (6) found that only FEV 1 /FVC% was significantly different between the studied and comparative groups (Z = -2.02. p = 0.04). Significant value for FEV 1 /FVC% showed that there was airway obstruction for lung function among the studied group compared with the comparative group.…”
Section: Respiratory Health Symptoms and Lung Function Abnormalitymentioning
confidence: 89%
“…Regards to Malaysia climate, these compilations has originate immensely among children and preschooler [7][8][9][10]. Whereas it enormously affected by the weather [7], indoor air, ventilation strategies [7][8][9] or the surrounding environment [10].…”
Section: Introductionmentioning
confidence: 99%